Management Planning In Transport - Perić, Teodor; Lorković, Andreja; Vučić, Dalibor (Promet - Traffic&Transportation, 2004)
Management planning in traffic and other activities includesa choice of missions and goals, as well as actions undertakenfor their realisation. It requires decision-making, that is,a choice among alternative trends of future actions. Therefore,planning and control are closely related.There are several types of plans: purposes or missions,goals, strategies, policies, procedures, rules, programs and calculations.Once managers become aware of the opportunities, they rationallyplan the setting of the goals and assumptions about thecurrent and future environment, finding and evaluating alternativetrends, and selecting the one that is to be followed.Therefore, planning means looking ahead and controlmeans looking backwards. The concept of overall planning,thus including traffic planning, illustrates the approach to managementwhich is based on the achieved goals.